DARKNESS: A Microwave Kinetic Inductance Detector Integral Field Spectrograph for High-contrast Astronomy. (16th April 2018) - Meeker, Seth R.; Mazin, Benjamin A.; Walter, Alex B.; Strader, Paschal; Fruitwala, Neelay; Bockstiegel, Clint; Szypryt, Paul; Ulbricht, Gerhard; Coiffard, Grégoire; Bumble, Bruce; Cancelo, Gustavo; Zmuda, Ted; et al.
Abstract: We present DARKNESS (the DARK-speckle Near-infrared Energy-resolving Superconducting Spectrophotometer), the first of several planned integral field spectrographs to use optical/near-infrared Microwave Kinetic Inductance Detectors (MKIDs) for high-contrast imaging. The photon counting and simultaneous low-resolution spectroscopy provided by MKIDs will enable real-time speckle control techniques and post-processing speckle suppression at frame rates capable of resolving the atmospheric speckles that currently limit high-contrast imaging from the ground. DARKNESS is now operational behind the PALM-3000 extreme adaptive optics system and the Stellar Double Coronagraph at Palomar Observatory. Here, we describe the motivation, design, and characterization of the instrument, early on-sky results, and future prospects.